Dynamic Forces between the Rails and the Wheels of Railway Vehicle - Peran, Zdravko (Promet - Traffic&Transportation, 2016)
The process of acquisition of the measured dynamic values of forces between the rails and the wheels on the real measurement train and the train tracks. The conversion of the measured values into the matrices and vectors enables numerous exact qualitative and quantitative studies of the dynamic phenomena behaviour. The paper shows the possibilities of using MATLAB computer tool. All the commands in the software are given and explained. Calculating of the empirical, normal and cumulative distribution on an example of the lateral force is given in detail. The new software is exactly verified mathematically and qualified for any further use. The developed software is the tool for the development of other two phases: software for the exact automatic evaluation of the maximum values of the dynamic values and software for the automatic approval of vehicles and railway due to the driving safety, loading tracks and driving comfort compared to the limited values regarding UI C CODE 518.